2019
DOI: 10.1021/acsnano.9b03165
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Sandwich Stable Perovskite Quantum-Dot Light-Emissive Ultrasensitive and Ultrafast Broadband Vertical Phototransistors

Abstract: Dual-functional devices that can simultaneously detect light and emit light have a tremendous appeal for multiple applications, including displays, sensors, defense, and high-speed optical communication. Despite the tremendous efforts of scientists, the progress of integration of a phototransistor, where the built-in electric field separates the photogenerated excitons, and a light-emitting diode, where the radiative recombination can be enhanced by band offset, into a single device remains a challenge. Combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 64 publications
6
59
0
Order By: Relevance
“…33 Chen and colleagues recently reported graphene sandwich stable PNC light-emissive ultrasensitive and ultrafast broadband phototransistors. 34 Herein, we report a detailed electron transfer study using single-walled CNTs and methylammonium lead halide PNCs. The preference of single-walled CNTs over C 60 fullerene is due to their superior electron transfer properties.…”
Section: Introductionmentioning
confidence: 99%
“…33 Chen and colleagues recently reported graphene sandwich stable PNC light-emissive ultrasensitive and ultrafast broadband phototransistors. 34 Herein, we report a detailed electron transfer study using single-walled CNTs and methylammonium lead halide PNCs. The preference of single-walled CNTs over C 60 fullerene is due to their superior electron transfer properties.…”
Section: Introductionmentioning
confidence: 99%
“…A time constant of about 3 ms is obtained, which is at least one order of magnitude faster than that of generally reported hybrid graphene-quantum dot photodetector. [25][26][27] The detectivity is also measured and calculated, and its value is about 3.8×10 9 cmHz 1/2 W -1 .…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…[22][23][24] However, the discrete energy structure of quantum dots makes its light absorption band narrow, which has limits for broadband detection. There is some work to improve the response of quantum-dot based devices, [25][26][27] but the performance in responsivity, response speed and response band generally cannot be optimized at the same time, and designed complex structure also increase difficulty for the fabrication and application, so much efforts is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bera et al reported light‐emissive vertical phototransistors based on perovskite QD and graphene, which can perform as broadband photodetector and light emitter within a single device ( Figure ). [ 186 ] High‐performance perovskite QDs acted as both exciton generator and recombination centers, which allowed the photodetection and the light emission, simultaneously, resulting in the EQE of 1.2 × 10 10 %, a photo‐responsivity of >10 9 A W −1 , and a response time of 20 μs. In addition, the device demonstrated a green emission with a quantum efficiency of 5.6%.…”
Section: Qd‐based Photonic Devicesmentioning
confidence: 99%